The waste heat recovery for power generation from automotive exhaust using Thermal-electric Cell (TEC) / Wan Ahmad Shahril Zulkifli - Zulkifli, Wan Ahmad Shahril (2017)
Road vehicle has a good potential for producing renewable energy from waste heat. The internal combustion process to move the vehicles had indirectly releasing waste heat into the environment which contributed to global warming. Thermal-electric Cell (TEC) is a device that able to convert thermal energy to electrical energy. The TECs system work when it is sandwiched between the hot side and cold side. The objective of this study is to investigate the possibility of generating power from waste heat using thermoelectric cell (TEC) with the effect of temperature difference experimentally. The experiment has been carried out in stagnation condition in the laboratory using 1500 cc petrol engine DOHC (4G91). Four TECs (SP1848-27145) were laid and connected in series on the top of exhaust muffler. The Arduino data tracking and 1750 Fluke Power Recorder has been employed to record the data. The experiment was run in two stages of cooling using air flow from standing fan and by attaching the cold water channel block on top of the TEC. Experimental results show that the highest voltage able to produce by the TEC was 2.42V in the range of temperature difference between 80°C and 85°C. By proving the electricity produced by the TEC, the result on the LED connected with the TEC start to light during output voltage was 1.80V. The performance of TEC is increased when the temperature difference between two sides is increased. Lastly, the conclusion has been made where the objectives of this project were achieved and the generated power could be utilized to extend the lifespan of the battery in the vehicle itself.